(untitled) (Journal of Engineering Science, 2024)
In this study, blended fabric like 65% polyester 33% rayon 2% spandex was naturally dyed utilizing coffee with maintaining of all the quality parameters. In the coffee-dyed fabric, carcinogenic element like formaldehyde was not detected. The bursting strength of the fabric was unchanged after dyeing and the fabric composition was identically tantamount. The color levelness of the dyed fabric was satisfactory and the color fastness to washing rating was 4-5. Colorfastness to perspiration in both acid and alkali medium was excellent containing a rating of 4-5. The naturally dyed fabric was able to hinder the microbial effect, and the entire dyeing procedure was convenient. Due to the absence of detrimental elements, the coffee-dyed fabric could be utilized to prepare hygienic garments items; baby wears products. The main function of this article is to enhance the functional properties of traditional fabric which is improving with the utilization of natural ingredients. Journal of Engineering Science 14(2), 2023, 15-20